Integrable Models of Interaction of Matter with Radiation - Inozemtsev, V.I.; Inozemtseva, N.G. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
The simplified models of interaction of charged matter with resonance modes of radiation generalizing the well-known Jaynes-Cummings and Dicke models are considered. It is found that these new models are integrable for arbitrary numbers of dipole sources and resonance modes of the radiation field. The problem of explicit diagonalisation of corresponding Hamiltonians is discussed.